Microstructural Study of Neodmium Nickelate Doped with Strontium Synthesized by Gelatin Method. (16th April 2013) - Oliveira, R. M. P. B.; Pimentel, P. M.; Araújo, J. H.; Melo, D. M. A.; Melo, M. A. F.; Martinelli, A. E.
Abstract : In this work nickelate nanoparticles were synthesized using a simple and fast new route, which makes use of gelatin as an organic precursor in order to evaluate the performance of the synthesis method to obtain materials and the influence of the strontium replacement on the structural parameters of the powders. Samples of Nd2- x Sr x NiO4 (x = 0 and 0.4) were calcined at 700 and 900 ° C at a heating of 10 ° C /min for 4 hours. X-ray powder diffraction patterns were obtained for all the samples, and the Rietveld Method was applied in order to determine the crystallite size using Scherrer's equation, the lattice parameters, and phase concentration. The results obtained using these techniques confirmed that the main crystal structure consists of the distorted K2 NiF4 -type tetragonal I4/mmm. In addition, scanning electron microscopy images revealed the formation of nanosized particles.